Association of BAX hypermethylation with coronary heart disease is specific to individuals aged over 70. Issue 4 (January 2019) - Zhang, Limei; Ji, Huihui; Huang, Yi; Hu, Haochang; Li, Bin; Yang, Yong; Yu, Hang; Chen, Xiaoying; Li, Wenxia; Liu, Fang; Wang, Shi; Wang, Chunming; et al.
Abstract: Introduction: As a member of B-cell lymphoma-2 (BCL-2) gene family, BCL-2 associated X ( BAX ) is important for cell apoptosis. In this work, we investigated the association of BAX promoter DNA methylation with coronary heart disease (CHD) in Han Chinese. Methods: A SYBR green-based quantitative methylation specific PCR (qMSP) was used to test BAX methylation levels in 959 CHD cases and 514 controls. Results: Although BAX methylation was not associated with CHD in the total samples, further breakdown analysis by age showed that BAX hypermethylation was significantly associated with CHD for individuals aged over 70 (median percentage of methylation ratio [PMR], 10.70% in cases versus (vs) 2.25% in controls, P =.046). Moreover, BAX methylation was associated with smoking and lipoprotein A (Lp(a)) for individuals aged over 70 (CHD: smoking P = .012, Lp(a) P = .001; non-CHD: smoking P = .051, Lp(a) P = .004). Further analysis of Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA) data showed BAX expression was upregulated by 5-aza-2'-deoxycytidine demethylation agent (fold = 1.66, P = .038) and inversely correlated with BAX methylation (r = −0.428, P = 8E-05). Conclusions: Our study supported that BAX hypermethylation might contribute to CHD risk via downregulation of BAX expression for individuals aged over 70. Abstract : Supplemental Digital Content is available in the text